165k views
3 votes
Here’s the question. Let me know when u have the answer. Also, this is just apart of a homework practice

Here’s the question. Let me know when u have the answer. Also, this is just apart-example-1
User Drown
by
5.4k points

1 Answer

3 votes

Let f(x) be a function; thus, the reflection across the y-axis of f(x) is given by f(-x).

Therefore, in our case,


g(x)=f(-x)=-(-x)^3-8(-x)^2-9(-x)+11

Simplifying,


\Rightarrow g(x)=x^3-8x^2+9x+11

Thus, the answer is g(x)=x^3-8x^2+9x+11, the first option (top to bottom).

User Zombies
by
5.0k points